Persistently strong Indonesian Throughflow during marine isotope stage 3: evidence from radiogenic isotopes. (15th March 2015) - Stumpf, Roland; Kraft, Steffanie; Frank, Martin; Haley, Brian; Holbourn, Ann; Kuhnt, Wolfgang
Abstract: The Indonesian Throughflow (ITF) connects the western Pacific Ocean with the eastern Indian Ocean, thus forming one of the major near surface current systems of the global thermohaline circulation. The intensity of the ITF has been found to be sensitive to changes in global ocean circulation, fluctuations in sea level, as well as to the prevailing monsoonal conditions of the Indonesian Archipelago and NW Australia. This study presents the first reconstruction of ITF dynamics combining radiogenic isotope compositions of neodymium (Nd), strontium (Sr), and lead (Pb) of the clay-size detrital fraction to investigate changes in sediment provenance, and paleo seawater Nd signatures extracted from the planktonic foraminifera and authigenic Fe–Mn oxyhydroxide coatings of the marine sediments focussing on marine isotope stage 3 (MIS3). Sediment core MD01-2378 was recovered within the framework of the International Marine Global Change Study (IMAGES) and is located in the area of the ITF outflow in the western Timor Sea (Scott Plateau, 13° 04.95′ S and 121° 47.27′ E, 1783 m water depth). In order to produce reliable seawater signatures, several extraction methods were tested against each other. The results of the study show that at this core location the extraction of surface water Nd isotope compositions from planktonic foraminifera is complicated by incomplete removal of contributions from Fe–Mn oxyhydroxides carrying ambient bottom water signatures. The bottom water Nd isotope signatures reliably obtained from the sediment coatings (average εNd = −5.0) document an essentially invariable water mass composition similar to today throughout the entire MIS3. The radiogenic Nd, Sr, and Pb isotope records of the clay-sized detrital fraction suggest that the Indonesian Archipelago rather than NW Australia was the main particle source at the location of core MD01-2378, and thus indicating a persistently strong ITF during MIS3. Furthermore, the variations of the detrital radiogenic isotopes are shown to be more sensitive to changes in circulation and document a somewhat enhanced ITF intensity during the early part of MIS3 until 47.4 ka compared with the remaining MIS3. Highlights: First ITF reconstruction combining detrital and authigenic isotope signatures. At the core site signatures of surface water cannot be separated from bottom water. Intermediate to deep waters remain unchanged in western Timor Sea during MIS3. Clay-size fraction of the sediment indicates a persistently strong ITF during MIS3.